Cruel delight : enlightenment culture and the inhuman - Steintrager, James A., 1965- (Indiana University Press, 2004)
Cruel Investigation investigates the fascination with joyful malice in 18th-century Europe and how this obsession helped inform the very meaning of humanity. James A. Steintrager reveals how the understanding of cruelty moved from an inexplicable, apparently paradoxical "inhuman" pleasure in the misfortune of others to an eminently human trait stemming from will and freedom